2002
DOI: 10.3928/0022-0124-20020101-06
|View full text |Cite
|
Sign up to set email alerts
|

Competence, Continuing Education, and Computers

Abstract: A survey of RNs in South Dakota was performed to determine their perceived level of competence, the extent to which their continuing nursing education (CNE) needs are being met, and their use of computers for CNE. Nationally certified nurses rated themselves significantly more competent than nurses who are not nationally certified. Fewer than half of the RNs reported their CNE needs were being met despite geographic access to CNE and programs available in their specialty. Three-fourths of nurses had computers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…Various types of innovative teaching technologies are described and investigated in higher education [11] [12] [13], [14], [15]. Analysis of scientific sources and own pedagogical experience allows to identify those pedagogical technologies which contribute greatly to the future dentists' professional competence formation.…”
Section: Innovative Technologies That Contribute To Future Dentists' mentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of innovative teaching technologies are described and investigated in higher education [11] [12] [13], [14], [15]. Analysis of scientific sources and own pedagogical experience allows to identify those pedagogical technologies which contribute greatly to the future dentists' professional competence formation.…”
Section: Innovative Technologies That Contribute To Future Dentists' mentioning
confidence: 99%
“…11) Distant learning is a fast, convenient, affordable and economical way of obtaining information [19]. It is successful in almost all areas, but there are a lot of discussions over its implementation in the medical field, due to concerns about deterioration in the quality of training [13]. Nevertheless, it is successfully used abroad.…”
Section: Innovative Technologies That Contribute To Future Dentists' mentioning
confidence: 99%
“…The most Anderson and Enge 359 Benner's novice to expert theory common barriers cited were lack of time to find educational information (Atack, 2003;Cobb, 2004;Dee & Stanley, 2005;Gregg & Wozar, 2003;Hegge, Poers, Hendrickx, & Vinson, 2002;Vought-O'Sullivan, Meehan, Havice, & Pruitt, 2006), lack of knowledge about computers, technology, the Internet and specific programs (Atack, 2003;Charles & Mamary, 2002;Cobb, 2004;Dee & Stanley, 2005;Gregg & Wozar, 2003;Hegge et al, 2002;Huckstadt & Hayes, 2005;Neafsey, 1997), and lack of administrative support from school officials in using technology to access information and evidence for practice (Adams, 2009;Spenceley, O'Leary, Chizawsky, Ross, & Estabrooks, 2008). Atack (2003), Dee and Stanley (2005), Gregg and Wozar (2003), and Hegge, Poers, Hendrickx, and Vinson (2002) found that some characteristics of computer use is problematic and presents a barrier. These characteristics include lack of access to a computer while away from the office and lack of remote access to databases such as the CINAHL and the National Library of Medicine (NLM), and lack of remote access to educational programs.…”
Section: Barriers To Technology Usementioning
confidence: 99%
“…The researchers concluded that poor access to computers and the Internet prevents nurses from searching for information online and from advancing their professional competence. Hegge, Powers, Hendricks and Vinson (2002) found that, 72.3% of the nurses in South Dakota had computers at home, and computers were available in 76% of the work places. Hughes and Pakieser (1999) found that computers lacking user-friendliness hampered the use of e-mail as a communication method among nurses.…”
Section: Literature Reviewmentioning
confidence: 99%